2022
DOI: 10.3389/fcell.2022.956394
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial autophagy in the sleeping brain

Abstract: A significant percentage of the mitochondrial mass is replaced on a daily basis via mechanisms of mitochondrial quality control. Through mitophagy (a selective type of autophagy that promotes mitochondrial proteostasis) cells keep a healthy pool of mitochondria, and prevent oxidative stress and inflammation. Furthermore, mitophagy helps adapting to the metabolic demand of the cells, which changes on a daily basis.Core components of the mitophagy process are PINK1 and Parkin, which mutations are linked to Parki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…Melatonin may induce mitophagy-associated regulators except NIX. In fact, several studies have revealed that melatonin enhances mitophagy by the PINK1-parkin pathway or autophagy-related genes in brain ischemia, acute brain injury, or Parkinson’s disease models all of which are quite different from glucocorticoid-induced neurodegeneration [ 52 , 54 ]. We did not screen for these pathways in other brain regions including substantia nigra or cortex, meaning that melatonin can alleviate glucocorticoid-induced impaired mitophagy by increasing PINK1-parkin pathways in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin may induce mitophagy-associated regulators except NIX. In fact, several studies have revealed that melatonin enhances mitophagy by the PINK1-parkin pathway or autophagy-related genes in brain ischemia, acute brain injury, or Parkinson’s disease models all of which are quite different from glucocorticoid-induced neurodegeneration [ 52 , 54 ]. We did not screen for these pathways in other brain regions including substantia nigra or cortex, meaning that melatonin can alleviate glucocorticoid-induced impaired mitophagy by increasing PINK1-parkin pathways in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial trafficking as well as autophagy (mitophagy) occur during sleep, probably explaining the reason most living beings require rest [ 154 ]. Interestingly, serotonin (5-HT) promotes mitochondrial transport in hippocampal neurons, suggesting that antidepressant drugs, serotonin reuptake inhibitors (SSRIs), may “exert their action by supplying healthy mitochondria to stressed neurons [ 155 ].…”
Section: Mitochondria and Aryl Hydrocarbon Receptormentioning
confidence: 99%
“…The clearance of these molecules is obviously vital, particularly in the case of the amyloid beta (Aβ) peptide, a byproduct mostly of membrane maintenance, which negatively affects neurons by coalescing into amyloid plaques, a key factor in the pathogenesis of AD and neurodegeneration in general [ 37 , 38 ]. The interplay between synaptic activity, mitochondrial function, and sleep is crucial in maintaining a healthy brain [ 39 ]. Sleep abnormalities can disrupt the typical energy metabolism of cells, including those located within the brain.…”
Section: Memory Aging and Sleep Interactionmentioning
confidence: 99%